Ethnobotanical Study of Sirgunggu (Clerondendrum serratum L.): Usage for Gurah, Traditional Theurapical Practice in Kampung Giriloyo, Imogiri, Bantul - Sindi Farhana; Astrino Purmanna; Nisa Ulmah Mudah; Rika Istiqomah; Erica Nuralam (Kaunia: Integration and Interconnection Islam and Science, 2017)
Local people of Kampung Giriloyo, Imogiri uses Sirgunggu (Clerondendrum serratum L.) as the main ingredient for traditional theurapical practice Gurah. The capability of doing this theurapical practice were inherited from one generation to generation so that become the tradition of Kampung Giriloyo and become the identity of Imogiri. This study aimed to know the usage of Sirgunggu as the main ingredient of traditional theurapical practice gurah and to know the conservation effort by the local people.